The Role of The Class Teacher in Forming The Profile of Pancasila Students in Civic Education Class for Grade IV Students of Al-Azhar Islamic Primary School 15 Pamulang - Hayati, Mustainah; Masyithoh, Siti (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2024)
In the 21st century, the existence of independent learning is very relevant to students' needs. It is hoped that the presence of an independent curriculum can improve the quality of education in Indonesia. Nadiem Makarim as Minister of Education and Culture of the Republic of Indonesia made the Pancasila Student Profile the vision and mission of Education and Culture of the Republic of Indonesia as stated in Minister of Education and Culture Regulation Number 22 of 2020. The values of the Pancasila student profile are: faith, devotion to God Almighty, global diversity, global diversity, mutual cooperation, independence, critical reasoning and creativity. This research aims to find out the role of class teachers in forming the character profile of Pancasila students at Al-Azhar 15 Pamulang Islamic Elementary School. This research uses descriptive qualitative methods. data collection techniques in observational research, interviews and documentation. The technical analysis used is triangulation. The results of this research suggest that the role of class teachers in forming the character profile of Pancasila students has gone well, because the school culture is in accordance with the values of the Pancasila student profile. There are 5 roles of class teachers in forming the profile of Pancasila students, namely: 1). The teacher provides understanding. 2) the teacher carries out habituation. 3). The teacher provides an example. 4) the teacher gives punishment. 5). The teacher reflects. The supporting factor for the role of class teachers in forming the character profile of Pancasila students is that there is good cooperation between local residents and parents. And the inhibiting factor in the role of class teachers in forming the character profile of Pancasila students is the limited supervision time at school and teachers must be consistent in reminding students.